Application of foreign law in Civil and Commercial Code, with special reference to cultural elements (Prudentia Iuris, 2017)
This paper analyzes application of foreign law in the Civil and Commercial Code and if it is receipted the theory of legal use, its content and scope, with special emphasis on the problem of rules adaptation made from methodological pluralism of Private International Law, with special reference to the cultural elements in resolving the case and what our approach should be implementation. Methodological pluralism gives better solutions to solving the problem of adaptation of the standard and it is justice for the case to take into account cultural and interpersonal elements of the case.
Keywords: Law Foreign; Application; Multiculturalism